(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The traditional medicine of India, Ayurveda, discusses the use of herbals for beauty, which is based on conventional wisdom. An effective and powerful technology in the cosmetics field is herbal cosmetics. There is nothing more ancient than humanity and civilization than the concept of beauty and cosmetics. Therefore, many of them use beauty products which contain herb that order to keep their beauty and youth. Nowadays, organic cosmetics are becoming more accessible to the common people since they are expected to have fewer side effects, as well as an increased level of safety and security. We aim in this study to develop a general-use herbal oil in which a variety of herbs that are readily available to us are utilized and evaluation of the herbal oil formulation was conducted by determining various parameters, such as viscosity, saponification value, pH, etc.